Photocatalytic degradation of methylene blue under visible light irradiation by non-peripherally tetra substituted phthalocyanine-TiO2 nanocomposites - Gorduk, Semih; Avciata, Oguzhan; Avciata, Ulvi (ELSEVIER SCIENCE SA, 2018)
In this study, novel 2-hydroxymethyl-1,4-benzodioxane substituted phthalonitrile ligand (1) and its non-peripherally tetra-substituted phthalocyanine derivatives with metal-free (2), zinc(II) (3), cobalt(II) (4), nickel(II) (5) and copper(II) (6) were synthesized. These compounds were characterized by several techniques including elemental analysis, FT-IR, UV-vis, H-1-NMR, C-13-NMR, GC-MS and MALDI-TOF MS. The TiO2 nanocomposites of these phthalocyanines (Pcs) were synthesized via the hydrothermal method in the presence of titanium(IV) isopropoxide. These nanocomposites were also characterized by FT-IR, XRD, FEG-SEM, EDX, UV-DRS and BET techniques. By monitoring the UV-vis absorption spectra, we found all the nanocomposites to have significant photocatalytic activities on methylene blue (MB), a common organic pollutant, under visible light irradiation (250 W). All the phthalocyanine-TiO2 nanocomposites have similar activities within the range of 100-140 min for full degradation (100%). Furthermore, the reusability studies showed the maintaining of more than 76% of the activity even after 5 recycles. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; TiO2; Photocatalytic activity; Nanocomposite; Degradation; TIO2 THIN-FILMS; TITANIUM-DIOXIDE; SPECTROELECTROCHEMICAL PROPERTIES; DOPED TIO2; DYE; METAL; WATER; IRON; 4-CHLOROPHENOL; SEMICONDUCTOR; Chemistry